SANDWICH ROOF PANELS TO SERVE AS THERMAL COLLECTORS - Bellay, Péter (2023)
The subject of the present application is an arrangement of sandwich panels already used in buildings in a way that makes them capable of collecting solar radiation and ambient heat and transferring the energy out of the roof. The structural elements of the present invention consist of a heat insulating core sandwiched between external and internal sheets with load-bearing capacity, similar to the make-up of the known load-bearing sandwich panels. Whether the sheet profiles are placed in the direction of the ridge beam or of the rafters, with the appropriate set of them, hollow structure is created on the surface and in the core of the panel in the direction of the rafters, in the entire length of the roof, functioning as pathways for gaseous materials (air ducts (1, 4)). If these air ducts, both external and in the core, are connected at the end facing each other, i.e. at the upper air turn chamber (8), the substance in them will start to flow on its own using solely gravitational forces in reaction to heat reaching the panel's external surface, i.e. the external profiled metal sheet (2). If a given point of the panel is cooled by heat exchanger (6), the spontaneous flow will remain continuous. Cooling transports the heat collected in the air ducts (hot air duct (1) and cold air duct (4)) out of the system, and this heat is utilized to provide for our energy needs. The subject of the application is, therefore a sandwich panel which functions as a thermal collector, hereinafter heat collector sandwich panel (3), which serves as the roof structure of a building, or is an integral part of the roof structure and meets without fail all protection requirements set for roof constructions. Due to its special design it is capable of collecting ambient heat, and transferring this heat to heat storage by the use of compatible, known auxiliary appliances.